Sustainable Electromagnetic Culinary Interface with Dual-Phase Filtration for Energy Efficiency and Environmental Impact Reduction - Vishwajit. V. Jade; Prathamesh. P. Mandavkar; Atharv. M. Nevrekar; Aditya. R. Panchal; Gajanan. P. Khapre (International Journal of Electrical Machine Analysis and Design, 2025)
Induct Net is an innovative kitchen appliance that seamlessly integrates advanced cooking technology with an inbuilt chimney system, marking a significant step towards sustainable culinary environments. This space-efficient device prioritizes energy efficiency, user safety, and environmental responsibility through its incorporation of internet of things (IoT) technology. Induct Net features a dual-filtration system with removable grease and charcoal filters, ensuring optimal performance while reducing waste. The IoT connectivity facilitates real-time monitoring, automatic chimney fan control, and timely notifications to the user’s mobile device, minimizing energy consumption. By focusing on sustainability and intelligent design, Induct Net redefines the cooking experience and sets a benchmark for co-friendly kitchen solutions.
Keywords: Induction; Internet of things (IoT); connectivity; culinary innovation; dual filtration system; energy efficiency; inbuilt chimney; induction technology; smart kitchen; user safety